Efek Mediasi Citra Merek pada Pengaruh Green Product Terhadap Keputusan Pembelian Konsumen Yotta di Kota Makassar - Muh. Yaqhzan; M. Ikhwan Maulana Haeruddin; M. Ilham Wardhana H.; Isma Azis Riu; Rahmat Riwayat Abadi (Journal Of Business, Finance, and Economics (JBFE), 2025)
This research aims to determine the mediating effect of brand image on the influence of green products on consumer purchasing decisions of Yotta in Makassar City. This study uses a type of quantitative research with a descriptive approach. The population in this study was unknown and the sample used amounted to 100 respondents. The sampling technique used purposive sampling. Data collection was carried out using observation and questionnaire methods. The data analysis technique used is Partial Least Square (PLS) using SmartPLS 4 software. The results showed that green products have a positive and significant effect on Yotta's consumer purchasing decisions in Makassar City, green products have a positive and significant effect on Yotta's brand image in Makassar City, brand image has a positive and significant effect on Yotta's purchasing decisions in Makassar City, and brand image is able to mediate the effect of green products on Yotta's consumer purchasing decisions in Makassar City.